Ambiente de aprendizagem de programação imperativa no ensino técnico: uma proposta de ensino em espiral - Oliveira, Bruno de (2021)
Programming teaching has faced challenges in its learning process since its conception. Among these challenges, there are the high dropout rate, the students' lack of motivation and the difficulty in understanding the fundamental concepts. To the technical education it is possible to add the lack of understanding of the course objectives, the incompleteness of primary knowledge provided by the basic education and the lack of previous experiences in programming and building algorithms. This research aims at investigating the process of acquiring a programming language in novices, establishing a theoretical model that contemplates the fundamentals of programming categorized by its complexity and proposing a spiral teaching where it is possible to establish the learning stage that the novice finds themself. Fundamentals of programming in their theoretical conceptual aspect were examined in the field of computing as well as the academic papers on the difficulties and teaching proposals in programming. In the field of education, theories of meaningful learning and the spiral curriculum were examined, as well as general theories of knowledge construction. As a result, the TFR structure (Type, Function, Route) was obtained, which describes the main activities carried out at the time of programming. TFR explains the fundamentals of imperative programming and categorizes in each of its pillars the degrees of complexity corresponding to its intrinsic concepts. Through a spiral teaching proposal applied to the TFR structure, it is possible to identify, in the process of acquiring a programming language, the stage in which the novice is, in addition to enabling discussions about the planning of classes, the sequence of teaching, and ways of presenting and evaluating the fundamental concepts of programming